Achieving Resectability in Giant Primary Breast Leiomyosarcoma Via Transarterial Chemoembolization: A Novel Neoadjuvant Strategy - Alfred Hamonangan L Toruan; Kiki A Rizki (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Primary leiomyosarcoma (LMS) of the breast is an exceptionally rare and aggressive non-epithelial malignancy, constituting less than 0.1% of all breast neoplasms. Due to the scarcity of cases, no standardized consensus exists regarding neoadjuvant protocols. Large, locally advanced tumors often present with chest wall fixation, rendering upfront resection difficult or impossible without extensive morbidity. This study explores the novel application of Transarterial Chemoembolization (TACE)—traditionally reserved for hepatic malignancies—as a neoadjuvant strategy to downstage a giant breast LMS. Case presentation: We present the case of a 40-year-old female presenting with a rapidly enlarging, painless, giant mass in the right breast measuring 19 x 18 x 15 cm. Clinical and radiological evaluation (CT Thorax) revealed a heterogeneous, hypervascular mass fixed to the pectoralis major muscle, classified as BIRADS 5. Core needle biopsy confirmed high-grade Leiomyosarcoma. Due to the tumor’s size and fixation to the chest wall, the patient underwent preoperative TACE using 35 mg Doxorubicin followed by embolization of the supplying branches of the right internal mammary and thoracoacromial arteries. Post-procedure, the tumor volume significantly decreased (downsized to approx. 15 cm), and critically, the mass detached from the chest wall, becoming mobile. The patient subsequently underwent a successful total mastectomy with clear margins (R0 resection). Conclusion: TACE offers a promising, minimally invasive neoadjuvant alternative for hypervascular, giant breast sarcomas. By inducing tumor necrosis and reducing vascularity, TACE can facilitate resectability in initially fixed tumors, potentially converting inoperable cases into candidates for R0 resection while minimizing intraoperative blood loss.